2009
DOI: 10.1371/journal.pone.0006380
|View full text |Cite
|
Sign up to set email alerts
|

Several Distinct Polycomb Complexes Regulate and Co-Localize on the INK4a Tumor Suppressor Locus

Abstract: Misexpression of Polycomb repressive complex 1 (PRC1) components in human cells profoundly influences the onset of cellular senescence by modulating transcription of the INK4a tumor suppressor gene. Using tandem affinity purification, we find that CBX7 and CBX8, two Polycomb (Pc) homologs that repress INK4a, both participate in PRC1-like complexes with at least two Posterior sex combs (Psc) proteins, MEL18 and BMI1. Each complex contains a single representative of the Pc and Psc families. In primary human fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 71 publications
6
118
0
Order By: Relevance
“…RYBP-PRC1 complexes are able to associate with chromatin independently (39) and contain unique compositions that are associated with different PcG targets (9). It has also been demonstrated that different PRC1 complexes can be observed at the same locus, such as at the INK4A/ARF locus, although the functional significance of these different complexes coexisting at promoters has not been fully characterized (40).…”
Section: Discussionmentioning
confidence: 99%
“…RYBP-PRC1 complexes are able to associate with chromatin independently (39) and contain unique compositions that are associated with different PcG targets (9). It has also been demonstrated that different PRC1 complexes can be observed at the same locus, such as at the INK4A/ARF locus, although the functional significance of these different complexes coexisting at promoters has not been fully characterized (40).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, knockdown of the polycomb components CBX7, CBX8, BMI1 or MEL18 results in INK4A derepression and proliferative arrest. (Jacobs et al, 1999;Itahana et al, 2003;Gil et al, 2004;Dietrich et al, 2007;Maertens et al, 2009). Interestingly, polycomb group proteins are also essential for stem cell self-renewal in both mice and humans (Lessard and Sauvageau, 2003;Molofsky et al, 2003;Park et al, 2003;Cales et al, 2008), and this is in part due to their ability to bind and repress the INK4A-ARF locus.…”
Section: Transcriptional Regulation Of the Ink4a-arf Locusmentioning
confidence: 99%
“…CBX8, part of the polycomb group repressive complex 1, belongs to the CBX protein family, which is homologous to the Drosophila polycomb protein (17) and regulates the proliferation of diploid human and mouse fibroblasts through direct binding to the INK4A-ARF locus (18). Furthermore, a previous study demonstrated that the ectopic expression of CBX8 leads to cellular immortalization (19).…”
Section: Discussionmentioning
confidence: 99%